Complicated Hydatid Cyst of Ulna- A Rare Case Report - Reddy, I V (J Clin Diagn Res, 2017)
Although hydatidosis is not uncommon in tropical countries, still bony involvement is comparatively rare. The aetiological agent is Echinococcus granulosus, a parasite belonging to cestode group with dog as definitive host and man as incidental host. We present a case of young male, who consulted us for painless, multiple swellings in his right forearm of three years duration, with restricted wrist movements. On examination multiple non tender, soft to firm swellings were noted with restricted terminal pronation. X-rays and MRI of right forearm showed multiple lobulated soft tissue components in intermuscular, subcutaneous and cutaneous planes and the main ulnar intramedullary cystic mass extending out as extramedullary cyst through proximal ulnar cortical breach. Proximal 2/3(rd) radius were also affected. On surgical exploration of forearm, cystic swelling measuring 8 × 6 × 5 cm sprouting out from proximal ulnar erosion was found. Intraoperative histopathology showed multiple endocysts suggestive of hydatid cyst; hence with protective measures wound closed back in layers and six weeks of oral albendazole 400 mg daily was given. At six weeks follow-up wrist movements improved but serous discharge persisted at drain site. Patient is still under regular follow-up. Thus, a differential diagnosis of bony hydatidosis should be considered while evaluating soft tissue swellings.